2022
DOI: 10.3390/nu15010030
|View full text |Cite
|
Sign up to set email alerts
|

Saturated Fatty Acid Chain Length and Risk of Cardiovascular Disease: A Systematic Review

Abstract: The purpose of this systematic review was to evaluate the impact of saturated fatty acid chain lengths on the development of cardiovascular disease (CVD). The importance of replacement macronutrients is also discussed. PubMed, CINAHL, and Cochrane library were searched for relevant prospective cohort studies that measured SFA chain length via diet analysis through October of 2020. A second updated PubMed search was conducted from October 2020 to 7 August 2022. Five prospective cohort studies were added. All st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 57 publications
(407 reference statements)
0
23
0
Order By: Relevance
“…Similar results were obtained in goat milk when a diet enriched with flaxseed and chia oil [ 30 , 40 ] and whole linseed and sunflower oil [ 25 , 41 ] were fed, which could be explained by their synthesis in the mammary from ruminal β-hydroxybutyrate [ 18 ]. Dairy lipids draw attention due to their impact on human health, given that myristic acid (C14:0) and palmitic acid (C16:0) have been linked to elevated blood cholesterol levels, potentially posing a risk for cardiovascular diseases [ 1 , 4 , 42 ]. Both CS and PS decreased the concentration of C14-C16 FA in sheep milk.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar results were obtained in goat milk when a diet enriched with flaxseed and chia oil [ 30 , 40 ] and whole linseed and sunflower oil [ 25 , 41 ] were fed, which could be explained by their synthesis in the mammary from ruminal β-hydroxybutyrate [ 18 ]. Dairy lipids draw attention due to their impact on human health, given that myristic acid (C14:0) and palmitic acid (C16:0) have been linked to elevated blood cholesterol levels, potentially posing a risk for cardiovascular diseases [ 1 , 4 , 42 ]. Both CS and PS decreased the concentration of C14-C16 FA in sheep milk.…”
Section: Discussionmentioning
confidence: 99%
“…The consumption of foods of animal origin containing saturated fatty acids (SFA) has been linked to an increased propensity for heart and coronary diseases because they can elevate serum levels of total cholesterol, and may raise contents of low-density lipoprotein [ 1 , 2 ]. In this sense, in ruminants, dietary factors can potentially favor the milk fatty acids (FA) profile, making it more suitable for human consumption [reducing SFA and increasing the desirable FA such as isomers of conjugated linoleic acid, especially rumenic acid and vaccenic acid, and α-linolenic acid, as well as improving the n6:n3 ratio] for human consumption [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…For chicken meat, the fatty acid composition and proportion are highly associated with its taste and nutritional value, and probably influence further storage and processing [ 23 ]. Excessive SFA consumption results in higher cholesterol levels, subsequently increasing the incidence of cardiovascular disease [ 32 ]. Excessive n-6 PUFA consumption increases in the incidence of obesity, inflammation, and cancer [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to Vergnaud et al, who assessed the association between the consumption of total meat, red meat, poultry, and processed meat in a large European population, higher poultry consumption was found to be associated with a lower risk of obesity ( 93 ), whereas Maskarinec et al found a significant positive relationship between white meat consumption and obesity in Hawaii ( 94 ). Furthermore, a longitudinal study of ~90,000 adults whose dietary habits and anthropometric data were measured for 6.5 years showed a statistically significant relationship between the consumption of animal proteins and long-term weight gain ( 95 ).…”
Section: Discussionmentioning
confidence: 99%